Band offset and an ultra-fast response UV-VIS photodetector in γ-In2Se3/p-Si heterojunction heterostructures. Issue 52 (21st August 2018) - Fang, Y. X.; Zhang, H.; Azad, F.; Wang, S. P.; Ling, F. C. C.; Su, S. C.
Abstract : High-quality γ-In2 Se3 thin films and a γ-In2 Se3 /p-Si heterojunction were prepared using pulse laser deposition (PLD). Abstract : High-quality γ-In2 Se3 thin films and a γ-In2 Se3 /p-Si heterojunction were prepared using pulse laser deposition (PLD). The band offset of this heterojunction was studied by XPS and the band structure was found to be type II structure. The valence band offset (Δ E v ) and the conduction band offset (Δ E c ) of the heterojunction were determined to be 1.2 ± 0.1 eV and 0.27 ± 0.1 eV, respectively. The γ-In2 Se3 /p-Si heterojunction photodetector has high responsivity under UV to visible light illumination. The heterojunction exhibits highly stable photodetection characteristics with an ultrafast response/recovery time of 15/366 μs. The ultrafast response time was attributed to type II structure band alignment, which was good for the separation of electron–hole pairs and it can quickly reduce recombination. These excellent properties make γ-In2 Se3 /p-Si heterojunctions a promising candidate for photodetector applications.